Seams like murder - Hechtman, Betty, 1947- (Hechtman, Betty, 1947- Crochet mystery., 2016)
Molly sets up a series of classes where the Tarzana Hookers can pass on their skills to others but Sheila, the teacher of the most popular seminar, is getting stage fright. To ease Sheila's fears, the Hookers plan a practice class at CeeCee's mansion, but before the lesson begins, they stumble upon a dead body in the apartment above CeeCee's garage.